pH Regulation of Electrogenic Sugar/H+ Symport in MFS Sugar Permeases. - Andre Bazzone; M Gregor Madej; H Ronald Kaback; Klaus Fendler (PLoS ONE, 2016)
Bacterial sugar symporters in the Major Facilitator Superfamily (MFS) use the H+ (and in a few cases Na+) electrochemical gradients to achieve active transport of sugar into the cell. Because a number of structures of MFS sugar symporters have been solved recently, molecular insight into the transport mechanism is possible from detailed functional analysis. We present here a comparative electrophysiological study of the lactose permease (LacY), the fucose permease (FucP) and the xylose permease (XylE), which reveals common mechanistic principles and differences. In all three symporters energetically downhill electrogenic sugar/H+ symport is observed. Comparison of the pH dependence of symport at symmetrical pH exhibits broad bell-shaped pH profiles extending over 3 to 6 pH units and a decrease at extremely alkaline pH ≥ 9.4 and at acidic to neutral pH = 4.6-7.5. The pH dependence can be described by an acidic to neutral apparent pK (pKapp) and an alkaline pKapp. Experimental evidence suggests that the alkaline pKapp is due to H+ depletion at the protonation site, while the acidic pKapp is due to inhibition of deprotonation. Since previous studies suggest that a single carboxyl group in LacY (Glu325) may be the only side chain directly involved in H+ translocation and a carboxyl side chain with similar properties has been identified in FucP (Asp46) and XylE (Asp27), the present results imply that the pK of this residue is switched during H+/sugar symport in all three symporters.